NNT mediates redox-dependent pigmentation via a UVB- and MITF-independent mechanism - Allouche, Jennifer; Rachmin, Inbal; Adhikari, Kaustubh; Pardo, Luba M.; Lee, Ju Hee; McConnell, Alicia M.; Kato, Shinichiro; Fan, Shaohua; Kawakami, Akinori; Suita, Yusuke; Wakamatsu, Kazumasa; Igras, Vivien; et al. (Cell, 2021)
Ultraviolet (UV) light and incompletely understood genetic and epigenetic variations determine skin color. Here we describe an UV- and microphthalmia-associated transcription factor (MITF)-independent mechanism of skin pigmentation. Targeting the mitochondrial redox-regulating enzyme nicotinamide nucleotide transhydrogenase (NNT) resulted in cellular redox changes that affect tyrosinase degradation. These changes regulate melanosome maturation and, consequently, eumelanin levels and pigmentation. Topical application of small-molecule inhibitors yielded skin darkening in human skin, and mice with decreased NNT function displayed increased pigmentation. Additionally, genetic modification of NNT in zebrafish alters melanocytic pigmentation. Analysis of four diverse human cohorts revealed significant associations of skin color, tanning, and sun protection use with various single-nucleotide polymorphisms within NNT. NNT levels were independent of UVB irradiation and redox modulation. Individuals with postinflammatory hyperpigmentation or lentigines displayed decreased skin NNT levels, suggesting an NNT-driven, redox-dependent pigmentation mechanism that can be targeted with NNT-modifying topical drugs for medical and cosmetic purposes.
CRIS-Team Scopus Importer:2021-08-13
Keywords: melanosome; MITF; nicotinamide nucleotide transhydrogenase; pigmentation; redox regulation; UVB